actually it's (3n^2)/2 + 13n/2

Log in to add a comment

actually it's (3n^2)/2 + 13n/2

Log in to add a comment

(3*25^2+13*25/2)-(3*24^2+13*24/2)

=> (5625+212.5)-(5184+156)

=> 5837.5-5340

=497.5

=> (5625+212.5)-(5184+156)

=> 5837.5-5340

=497.5

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

n term sum = 3n²/2 + 13n/2

as we know that nth term = (Sum of nth term ) -( sum of (n-1)th term)

so

=(3×(25)²/2 +(13×25)/2) - ( 3×(24)²/2 + (13×24)/2)

= 1100 - 1020

= 80

1st term = 8

sum of 2 terms = 19

2nd term = 19 - 8= 11

so. difference = 11- 8 = 3